Dance/movement therapy and sexual abuse: assessment and intervention based on body-mind approaches - Engelhard, Einat Shuper (Dance/movement therapy, 2023)
"Dance Movement Therapy and Sexual Abuse addresses the vital role dance-movement therapy plays in helping survivors of sexual abuse. Comprised of 10 chapters, the book describes assessment, diagnosis and intervention techniques with child, adolescent, and adult survivors of sexual abuse. Using case studies, contributing experts in the field offer the reader a profound understanding of the therapeutic techniques related to movement and the body for the emotional treatment of situations of sexual abuse. The chapters delve into the healing components of treatment during childhood, adolescence, and adulthood, and combine psychodynamic understandings with body-mind theories, techniques from the area of somatic experience, and bio-energetic analysis. Full of in-depth and comprehensive therapeutic interventions using dance-movement therapy to treat sexual trauma, this book will be an essential resource for dance movement therapists and students of the creative arts therapies"--